2015
DOI: 10.1007/s13277-015-4305-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic landscape of recurrent ASXL1, U2AF1, SF3B1, SRSF2, and EZH2 mutations in 304 Chinese patients with myelodysplastic syndromes

Abstract: We determined the biological and prognostic significance of five recurrent genetic aberrations in Chinese patients with myelodysplastic syndromes (MDS). A total of 304 Chinese MDS patients were screened for known mutations in five genes (ASXL1, U2AF1, SF3B1, SRSF2, and EZH2) using next-generation sequencing. Of these, 97 patients (31.9 %) harbored at least one mutation in the five genes, and patients harboring these mutations had distinct clinical features. Incidence ratios for mutations in ASXL1, U2AF1, SF3B1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 29 publications
3
34
0
1
Order By: Relevance
“…Mutations in U2AF1 also occur in the closely related condition AML at a frequency of approximately 4% (18), as well as in lung adenocarcinoma and other cancers (18, 19). U2AF1 mutations are associated with a worse overall survival in MDS patients and a higher risk of transformation to AML (11, 20, 21). U2AF1 mutations almost exclusively occur in 2 highly conserved amino acid positions, S34 and Q157, within the 2 zinc finger domains of the protein (6).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in U2AF1 also occur in the closely related condition AML at a frequency of approximately 4% (18), as well as in lung adenocarcinoma and other cancers (18, 19). U2AF1 mutations are associated with a worse overall survival in MDS patients and a higher risk of transformation to AML (11, 20, 21). U2AF1 mutations almost exclusively occur in 2 highly conserved amino acid positions, S34 and Q157, within the 2 zinc finger domains of the protein (6).…”
Section: Introductionmentioning
confidence: 99%
“…mutations from 10 studies 13,15,16,18,20,[23][24][25][26][27] was 1.60 (95% CI:1.33-1.92, P <0.001); this demonstrated that U2AF1 mutations were a poor factor for longer-term survival in MDS patients. The tendency for OS in patients with and without U2AF1 mutations is shown in Figure 3f for each study.…”
Section: U2af1mentioning
confidence: 86%
“…HRs and 95% CIs for OS and LFS were also extracted from the included studies together with the number of patients which survived every year after diagnosis. If the article provided 19 Wu, 2016 20 Jung, 2016 17 Hwang, 2016 16 Kang, 2015 18 Hong, 2015 15 Kim, 2017 13 Tefferi, 2018 21 Hamilton, 2019 22 Xu, 2017 26 Tefferi, 2017 24 Heuser, 2017 23 Wu, 2013 25 Journal Genes Chromosomes…”
Section: Data Extractionmentioning
confidence: 99%
See 2 more Smart Citations